Acceleration of diverging runoff trends on the Third Pole - Wang, L.; Li, X.; Lutz, A.; Nepal, Santosh; Chen, D.; Yao, T.; Su, F.; Cuo, L.; Yao, Z.; Zhang, Y.; Hu, Z.; Huang, J.; et al. (Springer, 2025)
Quantifying long-term historical changes in river runoff from the vulnerable high-mountain Third Pole is critical for Asia’s water resources planning, but still unresolved from a coherent, regional perspective in the climate change context. Here we show that the mountain-outlet runoff generally experienced significant increases for the westerlies-dominated rivers (Indus, Amu Darya, Syr Darya, Tarim, Heihe, and, Shule) and insignificant declines for the monsoon-dominated rivers (Ganges, Brahmaputra, Mekong, and Salween) in the past half-century, largely driven by the enhanced westerlies and weakened Indian summer monsoon. Although the changing rates of runoff can be mostly explained by the varying precipitation minus evapotranspiration, the total water storage changes (e.g., regional glacier melting, groundwater depletion) cannot be neglected. After the year 1997, the contrasting changes in the westerlies- and monsoon-dominated regions have been remarkably accelerated, necessitating proactive adaptations to sustain regional water, ecology, and food security.